Spectral Differentiation and Mimetic Methods for Solving the Scalar Burger’s Equation - Bertha K. Rodriguez-Chavez; Yessica E. Zarate-Pedrera (Selecciones Matemáticas)
In the present work, the spectral differentiation method was studied to solve the scalar Burger’s partial differential equation. This equation has been of considerable physical interest as it can be regarded as a simplified version of the Navier-Stokes equations. Through this study, the spectral differentiation method and its convergence were described; additionally, the mimetic method and the use of the MOLE library for numerically solving the scalar Burger’s equation were presented.